Alanine aminopeptidase from Bacillus licheniformis E7 expressed in Bacillus subtilis efficiently hydrolyzes soy protein to small peptides and free amino acids. (1st August 2022) - Chen, Yahui; Zhang, Rongzhen; Zhang, Wenchi; Xu, Yan
Abstract: Extensive proteolysis has become an important approach to add value to local bioresources. Here, we isolated novel strain Bacillus licheniformis E7 from protein-rich soil. This strain produces an alanine aminopeptidase, PepN, the encoding gene for which was cloned using genome walking technology. Recombinant PepN was expressed in B. subtilis 168—extra- and intracellular (secreted) forms of the enzyme were obtained ( Bl PepN ex and Bl PepN in, respectively), which showed different enzymatic properties. Their activities toward Ala -p -nitroaniline were 401.3 ± 16.9 U/mg and 113.8 ± 3.4 U/mg, respectively. The enzymes maintained >80% relative activity after incubation at 8.0–9.0 for 2 days, and >80% relative activity after incubation at 45 °C for 1 h. Bl PepN ex had an approximately fourfold higher k cat / K M value for Ala- p -nitroanilines than Bl PepN in . When combined with an alkaline protease, Bl PepN ex and Bl PepN in showed similar hydrolytic effects to those of a commercial aminopeptidase. The combinations hydrolyzed soybean protein to approximately 75% peptides of <500 Da and 45% peptides of <150 Da; >2000 mg/L free amino acids were also produced. This work supplies an effective, safe aminopeptidase for improving the degree of hydrolysis of protein-rich materials to release multitudinous peptides and amino acids. Highlights: Screening of alanine aminopeptidase-producing Bacillus licheniformis E7. Gene sequence mining, expression and purification of alanine aminopeptidase. Thermostability, pH stability, NaCl resistance and half-life of recombinant enzyme. High activity and affinity towards the substrate Ala-pNA. Efficient soy protein hydrolysis to small peptides and free amino acids.